2015
DOI: 10.1371/journal.pone.0120938
|View full text |Cite
|
Sign up to set email alerts
|

Canolol Inhibits Gastric Tumors Initiation and Progression through COX-2/PGE2 Pathway in K19-C2mE Transgenic Mice

Abstract: 4-vinyl-2, 6-dimethoxyphenol (canolol) is an antioxidant phenolic compound extracted from crude canola oil. In current research, K19-C2mE transgenic mice, developing hyperplastic tumors spontaneously in the glandular stomach, were used to study the mechanisms involved in the anti-inflammation and anti-tumor effects of canolol. Tg mice receiving canolol diet had a reduced tumor incidence, to 41.2%, compared with Non-treatment Tg mice, 77.8% of which had gastric tumor (P=0.002). Besides that, the mean tumor diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Using transgenic mice, Pan et al showed that COX-2/PGE2 promotes lung tumor development via the MAPK pathway, cell proliferation and transformation were inhibited in K-ras/COX-2 -/- mice 36. Another study from Cao et al, using K19-C2mE transgenic mice, revealed that COX-2/PGE2 signal transduction was involved in the initiation and progression of gastric tumors 37. Moreover, overexpression COX-2 was correlated with poor prognosis for breast carcinoma patients 38.…”
Section: Discussionmentioning
confidence: 99%
“…Using transgenic mice, Pan et al showed that COX-2/PGE2 promotes lung tumor development via the MAPK pathway, cell proliferation and transformation were inhibited in K-ras/COX-2 -/- mice 36. Another study from Cao et al, using K19-C2mE transgenic mice, revealed that COX-2/PGE2 signal transduction was involved in the initiation and progression of gastric tumors 37. Moreover, overexpression COX-2 was correlated with poor prognosis for breast carcinoma patients 38.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, canolol with a very low concentration (5.6 μM) showed a protective effect against oxidative stress and apoptosis induced by H 2 O 2 in those cells. The newest in vivo research by Cao et al (2015) is in agreement with in vitro antitumor activity of canolol, because canolol diet reduced tumor incidence in K19-C2mE transgenic mice to 41.2% compared with nontreatment transgenic mice, 77.8% of which had gastric tumor. Due to its anti-inflammation and antitumor activity, they concluded that canolol could inhibit the gastritisrelated tumor initiation and progression (Cao et al, 2015).…”
Section: Anticancer Activity Of Canolol and The Canolol Dimermentioning
confidence: 66%
“…The newest in vivo research by Cao et al (2015) is in agreement with in vitro antitumor activity of canolol, because canolol diet reduced tumor incidence in K19-C2mE transgenic mice to 41.2% compared with nontreatment transgenic mice, 77.8% of which had gastric tumor. Due to its anti-inflammation and antitumor activity, they concluded that canolol could inhibit the gastritisrelated tumor initiation and progression (Cao et al, 2015). As there are some differences in the results obtained with various cell lines and possible positive (antioxidant, anticancer, and anti-inflammatory) as well as negative (cytotoxic) effects on cancer cells, but also normal cells, further research on canolol, including more in vivo studies, will surly contribute to safe and proper application of this potent phytochemical in the pharmaceutical and food industry.…”
Section: Anticancer Activity Of Canolol and The Canolol Dimermentioning
confidence: 66%
“…For the grade of COX-2, EP2, Gαs, and β-catenin expression, H score calculation was performed as previously described. 6 …”
Section: Histological and Immunohistochemical Analysesmentioning
confidence: 99%